Behavioral arrest and a characteristic slow waveform are hallmark responses to selective 5-HT2A receptor activation - April Contreras (Nature Portfolio, 2021)
Abstract Perception, emotion, and mood are powerfully modulated by serotonin receptor (5-HTR) agonists including hallucinogens. The 5-HT2AR subtype has been shown to be central to hallucinogen action, yet the precise mechanisms mediating the response to 5-HT2AR activation remain unclear. Hallucinogens induce the head twitch response (HTR) in rodents, which is the most commonly used behavioral readout of hallucinogen pharmacology. While the HTR provides a key behavioral signature, less is known about the meso level changes that are induced by 5-HT2AR activation. In response to administration of the potent and highly selective 5-HT2AR agonist 25I-NBOH in mice, we observe a disorganization of behavior which includes frequent episodes of behavioral arrest that consistently precede the HTR by a precise interval. By combining behavioral analysis with electroencephalogram (EEG) recordings we describe a characteristic pattern composed of two distinctive EEG waveforms, Phase 1 and Phase 2, that map onto behavioral arrest and the HTR respectively, with the same temporal separation. Phase 1, which underlies behavioral arrest, is a 3.5–4.5 Hz waveform, while Phase 2 is slower at 2.5–3.2 Hz. Nicotine pretreatment, considered an integral component of ritualistic hallucinogen practices, attenuates 25I-NBOH induced HTR and Phase 2 waveforms, yet increases behavioral arrest and Phase 1 waveforms. Our results suggest that in addition to the HTR, behavioral arrest and characteristic meso level slow waveforms are key hallmarks of the response to 5-HT2AR activation. Increased understanding of the response to serotonergic hallucinogens may provide mechanistic insights into perception and hallucinations, as well as regulation of mood.